Neuro-Glial and Systemic Mechanisms of Pathological Responses in Rat Models of Primary Blast Overpressure Compared to “Composite” Blast - Svetlov, Stanislav I.; Prima, Victor; Glushakova, Olena; Svetlov, Artem; Kirk, Daniel; Gutierrez, Hector; Serebruany, Victor; Curley, Kenneth; Wang, Kevin K.; Hayes, Ronald L. (Frontiers in Neurology, 2012)
A number of experimental models of blast brain injury have been implemented in rodents and larger animals. However, the variety of blast sources and the complexity of blast wave biophysics have made data on injury mechanisms and biomarkers difficult to analyze and compare. Recently, we showed the importance of rat position towards blast generated by an external shock tube. In this study, we further characterized blast producing moderate TBI and defined ‘composite’ blast and primary blast exposure set-ups. Schlieren optics visualized interaction between the head and a shock wave generated by external shock tube, revealing strong head acceleration upon positioning the rat on-axis with the shock tube (composite blast), but negligible skull movement upon peak overpressure exposure off-axis (primary blast). Brain injury signatures of a primary blast hitting the frontal head were assessed and compared to damage produced by composite blast. Low to negligible levels of neurodegeneration were found following primary blast compared to composite blast by silver staining. However, persistent gliosis in hippocampus and accumulation of GFAP/CNPase in circulation was detected after both primary and composite blast. Also, markers of vascular/endothelial inflammation integrin alpha/beta, sICAM, and L-selectin along with neurotrophic factor NGF-beta were increased in serum within 6 hours post-blasts and persisted for 7 days thereafter. In contrast, systemic IL-1, IL-10, fractalkine, neuroendocrine peptide Orexin A, and VEGF receptor Neuropilin-2 (NRP-2) were raised predominantly after primary blast exposure. In conclusion, biomarkers of major pathological pathways were elevated at all blast setups. The most significant and persistent changes in neuro-glial markers were found after composite blast, while primary blast instigated prominent systemic cytokine/chemokine, Orexin A, and Neuropilin-2 release, particularly when primary blast impacted rats with unprotected body.